Synthesis of substituted γ- and δ-lactams based on titanocene(iii)-catalysed radical cyclisations of trichloroacetamides. Issue 60 (8th June 2016) - Diaba, Faïza; Gómez-Bengoa, Enrique; Cuerva, Juan M.; Bonjoch, Josep; Justicia, José
Abstract : Straightforward synthesis of dehalogenated γ- and δ-lactams based on a Cp2 TiCl-catalysed radical cyclisation of trichloroacetamides under mild conditions. Abstract : A new procedure for the synthesis of γ- and δ-lactams based on a Cp2 TiCl-catalysed cyclisation of trichloroacetamides under mild reaction conditions is reported. Theoretical studies supported the observed regioselectivity in the cyclisations and the mechanism involved in the dehalogenation process.